High desalination seawater desalination composite reverse osmosis membrane and preparation method thereof

CN122912704APending Publication Date: 2026-10-16SHENZHEN XUHAI INVESTMENT CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611206068.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-10
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

[0004]起初,这种微界面应力并不会立即导致宏观性能变化,但随着运行时间的推移,微应力逐渐积累,引发以下微观结构损伤:聚酰胺层与支撑层之间的结合力不足以抵抗反复的剪切应力,导致局部界面分离,形成纳米级的空腔或缝隙;在拉伸应力集中区域,聚酰胺本体产生微米甚至纳米级的裂纹,破坏分离层的完整性;而上述微观损伤累积后表现为脱盐率缓慢下降、初始高通量优势衰减加快

Benefits of technology

本申请通过设置由温敏性聚合物与高导热二维纳米材料复合而成的热响应型应力缓冲中间层,如同“热机械弹簧”般吸收并耗散聚酰胺分离层与支撑层因热膨胀系数差异产生的交变剪切应力,实现自适应抵抗昼夜温差引起的界面热应力,并借助自修复型聚酰胺分离层中的修复微胶囊在昼夜冷热循环诱发纳米/微米裂纹时实现微损伤原位自修复,利用多层次、多功能一体化设计,能够得到一种兼具超高脱盐率、高水通量,且能够自适应抵抗昼夜温差带来的不利影响,并保持较佳应用稳定性的反渗透膜。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The application relates to the field of membrane separation technology and specifically discloses a high-desalination seawater desalination composite reverse osmosis membrane and a preparation method thereof. The high-desalination seawater desalination composite reverse osmosis membrane comprises a porous support layer, a thermal response type stress buffering intermediate layer and a self-repairing type polyamide separation layer arranged in sequence; the thermal response type stress buffering intermediate layer is composed of a temperature-sensitive polymer and high-thermal-conductivity two-dimensional nanomaterials; the self-repairing type polyamide separation layer is formed through interfacial polymerization of an aqueous phase solution containing a polyamine and an oil phase solution containing a polyacyl halide; the aqueous phase solution further contains repair microcapsules, the repair microcapsules are composed of a shell and a core material, the shell is polyurea, and the core material is a low-viscosity aromatic polyamine. The application can obtain a reverse osmosis membrane which has ultra-high desalination rate, high water flux, can self-adaptively resist the adverse effects caused by day-night temperature difference and can maintain good application stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of membrane separation technology, and more specifically, to a high-desalination seawater desalination composite reverse osmosis membrane and its preparation method. Background Technology

[0002] With the increasing scarcity of freshwater resources globally, seawater desalination technology has become an important way to solve the water crisis. Reverse osmosis (RO) membrane technology, due to its high efficiency and energy saving, has become the mainstream technology for seawater desalination. Currently, most commercially available reverse osmosis membranes are thin-film composite (TFC) membranes, typically composed of a non-woven fabric support layer, a porous polysulfone-based membrane, and an ultrathin polyamide active separation layer.

[0003] In seawater desalination projects in extreme climate regions, membrane modules experience significant diurnal temperature variations (daily temperature differences can reach 15-25℃) in actual operating environments. Due to the significant difference in thermal expansion coefficients between the polyamide layer and the porous support layer—the thermal expansion coefficient of the polyamide layer is usually much higher than that of the polysulfone or polyethersulfone support layer—micro-interfacial stress is generated. Affected by repeated diurnal temperature cycles, the membrane interface is in an alternating stress field for a long time.

[0004] Initially, this micro-interface stress does not immediately lead to changes in macroscopic performance. However, as the operating time increases, the micro-stress gradually accumulates, causing the following microstructural damage: the bonding force between the polyamide layer and the support layer is insufficient to resist repeated shear stress, resulting in local interface separation and the formation of nanoscale cavities or gaps; in areas of concentrated tensile stress, micron or even nanoscale cracks are generated in the polyamide body, destroying the integrity of the separation layer; and the accumulation of the above micro-damage manifests as a slow decrease in desalination rate and an accelerated decay of the initial high-throughput advantage.

[0005] Therefore, there is an urgent need to propose a solution to address the aforementioned technical problems. Summary of the Invention

[0006] In order to obtain a reverse osmosis membrane that has both ultra-high desalination rate and high water flux, can adaptively resist the adverse effects of diurnal temperature variation, and maintains good application stability, this application provides a high desalination seawater desalination composite reverse osmosis membrane and its preparation method.

[0007] In a first aspect, this application provides a high-desalination seawater desalination composite reverse osmosis membrane, employing the following technical solution: A high-desalination seawater desalination composite reverse osmosis membrane includes a porous support layer, a thermally responsive stress buffer intermediate layer, and a self-healing polyamide separation layer arranged sequentially. The thermally responsive stress-buffered intermediate layer is composed of a thermosensitive polymer and a highly thermally conductive two-dimensional nanomaterial; the thermosensitive polymer is a block copolymer of poly(N-isopropylacrylamide) and polyethylene glycol; the highly thermally conductive two-dimensional nanomaterial is boron nitride nanosheets or functionalized graphene oxide. The self-healing polyamide separation layer is formed by an interfacial polymerization reaction between an aqueous solution containing polyamines and an oil solution containing polyacrylamide halides. The aqueous solution also contains repair microcapsules, which are composed of a shell and a core material. The shell is polyurea and the core material is a low-viscosity aromatic polyamine.

[0008] By employing the above technical solution, during the high-temperature phase of daytime, the temperature-sensitive polymer chains contract, and the resulting tiny voids allow for minor expansion space in the film layer, releasing compressive stress. During the low-temperature phase of nighttime, the temperature-sensitive polymer chains expand, filling the voids, restoring the dense structure, and preventing interfacial debonding caused by cooling contraction. Thus, the temperature-sensitive polymer undergoes reversible swelling-contraction during heating / cooling, consuming alternating strain like a "thermomechanical spring." During this process, the highly thermally conductive two-dimensional nanomaterials can accelerate heat transfer between the film surface and the environment, reduce the temperature difference and thermal gradient stress across the film cross-section, prevent stress concentration in the polyamide layer due to localized overheating, and act as a "slip / decoupling" agent at the interface, hindering the cross-layer propagation of microcracks. By combining thermosensitive polymers and highly thermally conductive two-dimensional nanomaterials, a balance can be achieved between modulus, thermal conductivity, and interfacial bonding, reducing the effective thermal expansion mismatch between the polyamide separation layer and the support layer. At the same time, the PEG blocks in the thermally responsive stress-buffered interlayer have high hydrophilicity and can adsorb water molecules through hydrogen bonds, forming a "water channel bridge" between the polyamide layer and the support layer, reducing the interfacial energy barrier for water molecule transport across layers. The interlayer gaps of the highly thermally conductive two-dimensional nanomaterials can form sub-nanometer ordered channels, which can assist in the rapid transport of water molecules without sacrificing the desalination rate, thereby ensuring high water flux.

[0009] The self-healing polyamide separation layer forms a dense polyamide network through traditional interfacial polymerization (polyamines / polyacrylamide halides). The repair microcapsules are pre-installed in the aqueous phase and "frozen" to the polyamide matrix or subsurface during interfacial polymerization. The polyurea shell has good chemical compatibility with the polyamide environment and moderate mechanical strength, allowing it to rupture under stress at the crack tip. When diurnal thermal cycling induces nano / micro cracks, the shell ruptures, the core material flows out, and low-viscosity aromatic polyamine fills the gaps through capillary action, undergoing interfacial polymerization with surrounding residual acrylamide halide groups to form new amide bonds / polyurea crosslinking points, repairing crack integrity and effectively delaying macroscopic performance degradation. Furthermore, the repair microcapsules are "frozen" to the polyamide matrix or subsurface, rather than exposed on the separation surface, avoiding pore defects. The good chemical compatibility of the polyurea shell with the polyamide prevents the formation of additional permeation pathways, thus ensuring ultra-high desalination rates and high water flux.

[0010] In the aforementioned high-desalination seawater desalination composite reverse osmosis membrane, the self-healing polyamide layer ensures initial separation performance, and its microcracks trigger a repair mechanism; the thermally responsive buffer intermediate layer reduces the generation (stress dissipation) and propagation (decoupling interface) of microcracks, while also buying time for the repair layer; the high thermal conductivity two-dimensional nanomaterial homogenizes the temperature field, reduces the stress load on the intermediate layer and the separation layer, and makes the buffering efficiency of the temperature-sensitive polymer more stable; therefore, through the synergistic effect of the three mechanisms, a reverse osmosis membrane with ultra-high desalination rate, high water flux, adaptive resistance to the adverse effects of diurnal temperature differences, and good application stability can be obtained.

[0011] Preferably, in the thermosensitive polymer, the Mn of the poly(N-isopropylacrylamide) block is 1800-2200 Da, the Mn of the polyethylene glycol block is 10000-12000 Da, and the polydispersity index (PDI) of the thermosensitive polymer is ≤1.15.

[0012] By adopting the above technical solutions, the poly(N-isopropylacrylamide) block provides temperature-sensitive phase transition and viscoelastic buffering. The selection of Mn at 1800-2200 Da, with its suitable segment length, demonstrates excellent stress dissipation capabilities, ensuring a defined low critical dissolution temperature and a suitable phase transition range. This achieves excellent buffering effects of "absorbing energy during thermal expansion and rebounding during cold contraction," and exhibits good interfacial matching with the polyamide separation layer and support layer. The polyethylene glycol block mainly undertakes the functions of hydrophilic modification, supplying segment flexibility, smooth modulus transition, and mass transfer assistance. The selection of Mn at 10000-12000 Da provides long-range compliant segments to mitigate the abrupt change in the phase transition modulus of the poly(N-isopropylacrylamide) block, making the overall energy storage modulus of the intermediate layer change more smoothly with temperature, ensuring the uniformity of buffering performance, and improving the interfacial compatibility between the intermediate layer and the polyamide layer. A polydispersity index (PDI) ≤ 1.15 for the temperature-sensitive polymer ensures uniformity in film formation and interfacial stress distribution, while maintaining good service stability with the high thermal conductivity two-dimensional nanomaterial. Thus, through the synergistic effect of the above parameter combination, excellent management of the micro-interfacial stress between the polyamide separation layer and the support layer is achieved, ensuring the stability of the reverse osmosis membrane under diurnal temperature variations.

[0013] Preferably, in the thermally responsive stress buffer interlayer, the weight ratio of the temperature-sensitive polymer to the highly thermally conductive two-dimensional nanomaterial is (8.5-9.5):1.

[0014] By adopting the above technical solution, the temperature-sensitive polymer has a strong encapsulation and anchoring effect on the high thermal conductivity two-dimensional nanomaterial, reducing the risk of filler detachment or migration under long-term water flow scouring. Furthermore, the temperature-sensitive polymer as the main body achieves "soft buffering", and the high thermal conductivity two-dimensional nanomaterial as the auxiliary achieves "thermal homogenization + decoupling", avoiding functional imbalance caused by excessive amounts of either side, and ultimately achieving excellent thermal stress buffering and long-term structural stability.

[0015] Preferably, the thickness of the thermally responsive stress buffer interlayer is 60-80 nm.

[0016] By adopting the above technical solution, 60-80nm is the optimal thickness for the functional-structural-process synergy of the thermally responsive stress buffer intermediate layer: it ensures the full utilization of the viscoelastic energy dissipation of the temperature-sensitive polymer and the heat dissipation decoupling of the high thermal conductivity filler, while controlling the mass transfer resistance, interfacial stress and preparation difficulty within an acceptable range, ultimately achieving efficient buffering and long-term stability support for the micro-stress at the interface between the polyamide separation layer and the support layer under day and night temperature difference conditions.

[0017] Preferably, the mass fraction of the repair microcapsules in the self-healing polyamide separation layer is 1.5-3%.

[0018] By adopting the above technical solution, since the ultra-high desalination rate of the polyamide separation layer depends on a continuous, highly cross-linked dense network, excessive microcapsules will introduce defects or disrupt polymerization. The above range belongs to the "low disturbance range", which can embed the repair function without significantly changing the dynamics of the polyamide separation layer. At the same time, it can ensure sufficient repair microcapsule density to achieve damage repair coverage, thereby ensuring the excellent and stable operation of the self-healing polyamide separation layer.

[0019] Preferably, the repair microcapsules have a particle size of 40-60 nm and a shell thickness of 5-15 nm.

[0020] By adopting the above technical solution, the thickness of the polyamide active layer formed by interfacial polymerization is typically 100-200nm. Repair microcapsules of 40-60nm can be encapsulated in the polyamide subsurface or internode gaps without penetrating to the separation surface. Therefore, no through-hole non-selective macropores are formed, ensuring that the ultra-high desalination rate is not compromised. The shell thickness is 5-15nm, which not only protects the core material from leakage during preparation and storage, but also allows it to rupture in time under crack stress, releasing sufficient core material to fill the cracks. In this way, the self-healing polyamide separation layer can maintain both ultra-high desalination rate and high water flux, and can also perform in-situ, quantitative, and long-term repair of micro-damage under alternating diurnal temperature stress, ultimately improving the application stability of high-desalination seawater desalination composite reverse osmosis membranes.

[0021] Preferably, the low-viscosity aromatic polyamine is an oligomer of m-phenylenediamine with a number-average molecular weight of 250-320 g / mol, a degree of polymerization of 2-3, a dynamic viscosity of 20-35 mPa·s at 25°C, and an amine value ≥800 mg KOH / g.

[0022] By adopting the above technical solution, the core material is selected from m-phenylenediamine oligomers that are homologous to the main raw material of the polyamide separation layer. This ensures that there are no significant changes in composition or modulus at the repair interface, guaranteeing the long-term reliability of the self-healing function and the overall stability of the membrane. With a number-average molecular weight of 250-320 g / mol and a degree of polymerization of 2-3, the core material can be rapidly and fully spread and filled in the nanoscale confined space under capillary action, and can provide multiple crosslinking sites in the in-situ repolymerization reaction, effectively restoring the density and mechanical continuity of the separation layer. A dynamic viscosity of 20-35 mPa·s at ℃ ensures that the core material remains within the crack for a sufficient time to complete the in-situ crosslinking reaction, significantly improving repair efficiency and the utilization rate of the repair agent; an amine value ≥800 mgKOH / g ensures that even with extremely limited release, it can still provide sufficient crosslinking reaction sites for crack repair, ultimately achieving high-quality repair; and through the synergy of the above parameters, in-situ, efficient, and long-term repair of micro-damage to the polyamide separation layer by low-viscosity aromatic polyamines is achieved, ensuring the long-term stable operation of the reverse osmosis membrane under extreme temperature difference conditions.

[0023] Preferably, the polyamine in the aqueous solution is one or a combination of several of the following: m-phenylenediamine, p-phenylenediamine, o-phenylenediamine, pyromellitic triamine, piperazine, ethanolamine, and isopropanolamine.

[0024] Preferably, the polyacrylamide halide in the oil phase solution is one or a combination of several of the following: trimesoyl chloride, phthaloyl chloride, orthophthaloyl chloride, isophthaloyl chloride, biphenyl dimethyl chloride, and benzene disulfonyl chloride.

[0025] Secondly, this application provides a method for preparing a high-desalination seawater desalination composite reverse osmosis membrane, employing the following technical solution: A method for preparing a high-desalination seawater desalination composite reverse osmosis membrane includes the following steps: (1) Take a porous support layer and immerse it in a dispersion containing a temperature-sensitive polymer and a highly thermally conductive two-dimensional nanomaterial. After taking it out, dry and solidify it on the porous support layer to form a thermally responsive stress buffer intermediate layer. (2) Coat the surface of the thermally responsive stress buffer intermediate layer formed in step (1) with an aqueous solution containing polyamine and repair microcapsules. After the treatment is completed, remove the residual liquid on the surface. Then coat the same surface with an oil solution containing polyacryl halides. After the treatment is completed, remove the residual liquid on the surface. Heat treatment is performed to form a self-healing polyamide separation layer. Finally, immerse it in an aqueous glycerol solution for treatment. Take it out and dry it to obtain a high desalination seawater desalination composite reverse osmosis membrane.

[0026] In summary, this application has the following beneficial effects: This application utilizes a thermally responsive stress buffer intermediate layer composed of a temperature-sensitive polymer and a highly thermally conductive two-dimensional nanomaterial. This layer acts like a "thermomechanical spring," absorbing and dissipating the alternating shear stress caused by the difference in thermal expansion coefficients between the polyamide separation layer and the support layer. This enables the membrane to adaptively resist interfacial thermal stress caused by diurnal temperature variations. Furthermore, by employing repair microcapsules in the self-healing polyamide separation layer, the membrane can achieve in-situ self-repair of micro-damage when nano / micro cracks are induced by diurnal thermal cycles. Through a multi-layered, multi-functional integrated design, a reverse osmosis membrane can be obtained that possesses ultra-high desalination rate, high water flux, adaptive resistance to the adverse effects of diurnal temperature variations, and maintains excellent application stability. Detailed Implementation

[0027] The present application will be further described in detail below with reference to embodiments and comparative examples.

[0028] Unless otherwise specified, all raw materials used in the embodiments and comparative examples of this application are commercially available.

[0029] Preparation of repair microcapsules: Under dry nitrogen protection, low-viscosity aromatic polyamines and polyisocyanates (IPDI) were mixed, and 0.8 wt% of Span80 was added as an oil phase emulsifier. Ethyl acetate was used as an organic solvent to aid dissolution, resulting in solution A (where the core material accounted for 25% of the volume and the polyisocyanate concentration was controlled at 0.3 mol / L). Sodium dodecyl sulfate (0.65 wt%) was added to deionized water, and the pH was adjusted to 9 with sodium hydroxide to obtain solution B. Solution A was dropped into solution B under high-speed shearing to form a uniform O / W microemulsion, and the temperature was raised to 37℃ for 2 h. After the reaction, the repair microcapsules were obtained by centrifugation, washing, and drying.

[0030] Example Example 1

[0031] A high-desalination seawater desalination composite reverse osmosis membrane comprises a porous support layer, a thermally responsive stress-buffered intermediate layer, and a self-healing polyamide separation layer arranged sequentially, and is prepared by the following steps: (1) Take a porous support layer and immerse it in a dispersion containing a temperature-sensitive polymer and a highly thermally conductive two-dimensional nanomaterial. After taking it out, dry and solidify it on the porous support layer to form a thermally responsive stress buffer intermediate layer. (2) The aqueous solution containing polyamine and repair microcapsules is coated on the surface of the thermally responsive stress buffer intermediate layer formed in step (1). After 100s, the surface liquid is removed. Then, the oil solution containing polyacryl halogen is coated on the same surface. After 45s, the surface liquid is removed. The membrane is heat-treated at 50°C for 3min to form a self-healing polyamide separation layer. Finally, it is immersed in a 20% glycerol aqueous solution for 5min. After drying, a high desalination seawater desalination composite reverse osmosis membrane is obtained.

[0032] Note: In the above operation, the porous support layer is a non-woven fabric reinforced polysulfone ultrafiltration membrane with a molecular weight cutoff of 40,000.

[0033] In the above dispersion containing thermosensitive polymer and highly thermally conductive two-dimensional nanomaterial, the solvent used is obtained by mixing ethanol and water in a volume ratio of 85:15. The concentration of thermosensitive polymer is 0.3wt%, and the highly thermally conductive two-dimensional nanomaterial is boron nitride nanosheets with a thickness of 4nm, a sheet diameter of 300nm, and 5 layers.

[0034] The thermally responsive stress buffer interlayer is composed of a thermosensitive polymer and a highly thermally conductive two-dimensional nanomaterial. The thermosensitive polymer is a block copolymer of poly(N-isopropylacrylamide) and polyethylene glycol. In the thermosensitive polymer, the Mn of the poly(N-isopropylacrylamide) block is 2000 Da, the Mn of the polyethylene glycol block is 11000 Da, and the polydispersity index (PDI) of the thermosensitive polymer is ≤1.15. In this embodiment, the PDI is 1.05.

[0035] In the thermally responsive stress-buffered interlayer, the weight ratio of the temperature-sensitive polymer to the highly thermally conductive two-dimensional nanomaterial is 9:1. The thickness of the thermally responsive stress-buffered interlayer is 70 nm.

[0036] The self-healing polyamide separation layer is formed by interfacial polymerization of an aqueous solution containing polyamine and an oil solution containing polyacrylamide halides. The aqueous solution consists of the following components by mass concentration: 4 wt% polyamine, 3 wt% camphor sulfonic acid, 2.5 wt% triethylamine, 0.15 wt% sodium dodecyl sulfonate, and the balance being water, wherein the polyamine is m-phenylenediamine. The oil solution consists of the following components by mass concentration: 0.15 wt% polyacrylamide halides and the balance being n-hexane, wherein the polyacrylamide halides are trimesoyl chloride.

[0037] The aqueous solution also contains repair microcapsules, which consist of a shell and a core material. The shell is polyurea, and the core material is a low-viscosity aromatic polyamine. The mass fraction of the repair microcapsules in the self-healing polyamide separation layer is 2.25%. The particle size of the repair microcapsules is 50 nm, with a shell thickness of 10 nm. The low-viscosity aromatic polyamine is an oligomer of m-phenylenediamine with a number-average molecular weight of 285 g / mol, a degree of polymerization of 2, a dynamic viscosity of 27.5 mPa·s at 25 °C, and an amine value of 800 mg KOH / g.

[0038] Example 2

[0039] A high-desalination seawater desalination composite reverse osmosis membrane differs from Example 1 in that, in the temperature-sensitive polymer, the Mn of the poly(N-isopropylacrylamide) block is 1800 Da, and the Mn of the polyethylene glycol block is 10000 Da.

[0040] Example 3

[0041] A high-desalination seawater desalination composite reverse osmosis membrane differs from Example 1 in that, in the temperature-sensitive polymer, the Mn of the poly(N-isopropylacrylamide) block is 2200 Da, and the Mn of the polyethylene glycol block is 12000 Da.

[0042] Example 4

[0043] A high-desalination seawater desalination composite reverse osmosis membrane differs from Example 1 in that, in the temperature-sensitive polymer, the Mn of the poly(N-isopropylacrylamide) block is 1700 Da, and the Mn of the polyethylene glycol block is 9000 Da.

[0044] Example 5

[0045] A high-desalination seawater desalination composite reverse osmosis membrane differs from Example 1 in that, in the temperature-sensitive polymer, the Mn of the poly(N-isopropylacrylamide) block is 2300 Da, and the Mn of the polyethylene glycol block is 13000 Da.

[0046] Example 6

[0047] A high-desalination seawater desalination composite reverse osmosis membrane differs from Example 1 in that the weight ratio of temperature-sensitive polymer to highly thermally conductive two-dimensional nanomaterial in the thermally responsive stress buffer intermediate layer is 8.5:1.

[0048] Example 7

[0049] A high-desalination seawater desalination composite reverse osmosis membrane differs from Example 1 in that the weight ratio of temperature-sensitive polymer to highly thermally conductive two-dimensional nanomaterial in the thermally responsive stress buffer intermediate layer is 9.5:1.

[0050] Example 8

[0051] A high-desalination seawater desalination composite reverse osmosis membrane differs from Example 1 in that the weight ratio of temperature-sensitive polymer to highly thermally conductive two-dimensional nanomaterial in the thermally responsive stress buffer intermediate layer is 8:1.

[0052] Example 9

[0053] A high-desalination seawater desalination composite reverse osmosis membrane differs from Example 1 in that, in the thermally responsive stress buffer intermediate layer, the weight ratio of temperature-sensitive polymer to highly thermally conductive two-dimensional nanomaterial is 9:1.

[0054] Example 10

[0055] A high-desalination seawater desalination composite reverse osmosis membrane differs from Example 1 in that the thickness of the thermally responsive stress buffer intermediate layer is 60 nm.

[0056] Example 11

[0057] A high-desalination seawater desalination composite reverse osmosis membrane differs from Example 1 in that the thickness of the thermally responsive stress buffer intermediate layer is 80 nm.

[0058] Example 12

[0059] A high-desalination seawater desalination composite reverse osmosis membrane differs from Example 1 in that the mass fraction of the repair microcapsules in the self-healing polyamide separation layer is 1.5%.

[0060] Example 13

[0061] A high-desalination seawater desalination composite reverse osmosis membrane differs from Example 1 in that the mass fraction of the repair microcapsules in the self-healing polyamide separation layer is 3%.

[0062] Example 14

[0063] A high-desalination seawater desalination composite reverse osmosis membrane differs from Example 1 in that the mass fraction of the repair microcapsules in the self-healing polyamide separation layer is 1%.

[0064] Example 15

[0065] A high-desalination seawater desalination composite reverse osmosis membrane differs from Example 1 in that the mass fraction of the repair microcapsules in the self-healing polyamide separation layer is 3.5%.

[0066] Example 16

[0067] A high-desalination seawater desalination composite reverse osmosis membrane differs from Example 1 in that the repair microcapsules have a particle size of 60 nm and a shell thickness of 15 nm.

[0068] Example 17

[0069] A high-desalination seawater desalination composite reverse osmosis membrane differs from Example 1 in that the repair microcapsules have a particle size of 40 nm and a shell thickness of 5 nm.

[0070] Example 18

[0071] A high-desalination seawater desalination composite reverse osmosis membrane differs from Example 1 in that the low-viscosity aromatic polyamine is an oligomer of m-phenylenediamine with a number-average molecular weight of 250 g / mol, a degree of polymerization of 3, a dynamic viscosity of 20 Pa·s at 25°C, and an amine value of 905 mg KOH / g.

[0072] Example 19

[0073] A high-desalination seawater desalination composite reverse osmosis membrane differs from Example 1 in that the low-viscosity aromatic polyamine is an oligomer of m-phenylenediamine with a number-average molecular weight of 320 g / mol, a degree of polymerization of 2, a dynamic viscosity of 35 mPa·s at 25°C, and an amine value of 850 mg KOH / g.

[0074] Comparative Example Comparative Example 1 A high-desalination seawater desalination composite reverse osmosis membrane differs from Example 1 in that it does not use a thermally responsive stress buffer intermediate layer.

[0075] Comparative Example 2 A high-desalination seawater desalination composite reverse osmosis membrane differs from Example 1 in that the self-healing polyamide separation layer does not use repair microcapsules.

[0076] Comparative Example 3 A high-desalination seawater desalination composite reverse osmosis membrane differs from Example 1 in that it does not use a thermally responsive stress buffer intermediate layer, and does not use repair microcapsules in the self-healing polyamide separation layer.

[0077] Performance testing Test samples: The high desalination seawater desalination composite reverse osmosis membranes obtained in Examples 1-19 were used as test samples 1-19, and the high desalination seawater desalination composite reverse osmosis membranes obtained in Comparative Examples 1-3 were used as control samples 1-3.

[0078] Experimental method: Prepare a NaCl aqueous solution with a concentration of 32000ppm (3.2wt%) to simulate seawater salinity; simultaneously, load the high-desalination seawater desalination composite reverse osmosis membrane to be tested into the cross-flow test cell, introduce deionized water, and run at a low pressure of 0.25MPa for 5 minutes to purge the air from the system; then switch to the 32000ppm NaCl aqueous solution as the feed liquid, turn on the constant temperature bath to maintain the feed liquid temperature at 25℃, and increase the pressure to 5.5MPa, and run under pre-pressure for 1 hour under these conditions.

[0079] After pre-pressurization, samples were taken at the inlet and outlet, and the conductivity was measured using a conductivity meter. The conductivity was then converted into salt concentration, and the initial desalination rate was calculated.

[0080] The volume of permeate was collected using a graduated cylinder over a certain period of time, and the initial flux was calculated by combining the effective membrane area and operating pressure.

[0081] Next, set the temperature of the constant temperature bath to 15℃ and maintain it for 12 hours, then set the temperature to 35℃ and maintain it for 12 hours, then set the temperature to 25℃ and maintain it for 6 hours. This is recorded as one cycle. After continuing the above 500 cycles, calculate the desalination rate and flux after the cycle in the same way as above.

[0082] Finally, the desalination rate decay rate and flux decay rate were calculated. After completing the above tests on test samples 1-19 and control samples 1-3, the test results were recorded in Table 1.

[0083] Table 1. Test results of test samples 1-19 and control samples 1-3

[0084] It should also be noted that the initial desalination rate of the high-desalination seawater desalination composite reverse osmosis membranes in test samples 1-19 was ≥99.8%, and the initial flux was ≥55.2 (LMH / MPa), proving that they have ultra-high desalination rate and high water flux.

[0085] Combining Example 1 and Comparative Examples 1-3 with Table 1, it can be seen that by setting a thermally responsive stress buffer interlayer composed of a temperature-sensitive polymer and a highly thermally conductive two-dimensional nanomaterial, and by utilizing the repair microcapsules in the self-healing polyamide separation layer to achieve in-situ self-repair of micro-damage induced by diurnal thermal cycling, the application stability of the high-desalination seawater desalination composite reverse osmosis membrane can be significantly improved under diurnal temperature variations. If only the thermally responsive stress buffer interlayer or only the repair microcapsules are used, it is found that although they can bring about corresponding improvements, the improvement is limited, and the sum of the improvement effects brought by the individual application of the two is far less than that of the synergistic combination. Therefore, it can bring a significant improvement effect of 1+1>2.

[0086] Combining Examples 1 and 2-5 with Table 1, it can be seen that the Mn of the poly(N-isopropylacrylamide) block is 1800-2200 Da, and the Mn of the polyethylene glycol block is 10000-12000 Da. This not only achieves excellent buffering effects of "absorbing energy during thermal expansion and rebounding during cold contraction", but also ensures the uniformity of buffering performance. As a result, the thermally responsive stress buffer interlayer can play an excellent corresponding role. However, if the range exceeds the above range, it is found that the corresponding effect will be significantly reduced.

[0087] Combining Examples 1 and 6-9 with Table 1, it can be seen that when the weight ratio of the temperature-sensitive polymer to the high thermal conductivity two-dimensional nanomaterial is (8.5-9.5):1, the temperature-sensitive polymer as the main component can achieve "soft buffering," while the high thermal conductivity two-dimensional nanomaterial can be used as an auxiliary component to achieve "thermal homogenization + decoupling," resulting in excellent and stable performance. However, when the ratio exceeds the above range, the functional imbalance caused by the excessive amount of one component will lead to a significant loss in the application stability of the high desalination seawater desalination composite reverse osmosis membrane.

[0088] Combining Examples 1 and 12-15 with Table 1, it can be seen that the mass fraction of the repair microcapsules in the self-healing polyamide separation layer is 1.5-3%, which can ensure the excellent and stable operation of the final self-healing polyamide separation layer. However, if the mass fraction is lower or higher than the above range, the desalination rate and flux reduction rate of the obtained high desalination seawater desalination composite reverse osmosis membrane will show significant losses in the above tests.

[0089] This specific embodiment is merely an explanation of this application and is not intended to limit it. After reading this specification, those skilled in the art can make modifications to this embodiment without contributing any inventive step, but such modifications are protected by patent law as long as they fall within the scope of the claims of this application.

Claims

1. A high-desalination seawater desalination composite reverse osmosis membrane, characterized in that, It includes a porous support layer, a thermally responsive stress-buffered intermediate layer, and a self-healing polyamide release layer arranged sequentially. The thermally responsive stress-buffered intermediate layer is composed of a thermosensitive polymer and a highly thermally conductive two-dimensional nanomaterial; the thermosensitive polymer is a block copolymer of poly(N-isopropylacrylamide) and polyethylene glycol; the highly thermally conductive two-dimensional nanomaterial is boron nitride nanosheets or functionalized graphene oxide. The self-healing polyamide separation layer is formed by an interfacial polymerization reaction between an aqueous solution containing polyamines and an oil solution containing polyacrylamide halides. The aqueous solution also contains repair microcapsules, which are composed of a shell and a core material. The shell is polyurea and the core material is a low-viscosity aromatic polyamine.

2. The high-desalination seawater desalination composite reverse osmosis membrane according to claim 1, characterized in that: In the thermosensitive polymer, the Mn of the poly(N-isopropylacrylamide) block is 1800-2200 Da, the Mn of the polyethylene glycol block is 10000-12000 Da, and the polydispersity index (PDI) of the thermosensitive polymer is ≤1.

15.

3. The high-desalination seawater desalination composite reverse osmosis membrane according to claim 1, characterized in that: In the thermally responsive stress buffer intermediate layer, the weight ratio of the temperature-sensitive polymer to the highly thermally conductive two-dimensional nanomaterial is (8.5-9.5):

1.

4. The high-desalination seawater desalination composite reverse osmosis membrane according to claim 1, characterized in that: The thickness of the thermally responsive stress buffer interlayer is 60-80 nm.

5. The high-desalination seawater desalination composite reverse osmosis membrane according to claim 1, characterized in that: The repair microcapsules have a mass fraction of 1.5-3% in the self-healing polyamide separation layer.

6. The high-desalination seawater desalination composite reverse osmosis membrane according to claim 1, characterized in that: The repair microcapsules have a particle size of 40-60 nm and a shell thickness of 5-15 nm.

7. The high-desalination seawater desalination composite reverse osmosis membrane according to claim 1, characterized in that: The low-viscosity aromatic polyamine is an oligomer of m-phenylenediamine with a number-average molecular weight of 250-320 g / mol, a degree of polymerization of 2-3, a dynamic viscosity of 20-35 mPa·s at 25°C, and an amine value ≥800 mg KOH / g.

8. The high-desalination seawater desalination composite reverse osmosis membrane according to claim 1, characterized in that: The polyamine in the aqueous solution is one or a combination of several of the following: m-phenylenediamine, p-phenylenediamine, o-phenylenediamine, mesitylenetriamine, piperazine, ethanolamine, and isopropanolamine.

9. The high-desalination seawater desalination composite reverse osmosis membrane according to claim 1, characterized in that: The polyacryl halogen in the oil phase solution is one or a combination of several of the following: pyromellitic chloromethyl chloride, phthaloyl chloride, orthophthaloyl chloride, isophthaloyl chloride, biphenyl chloromethyl chloride, and benzene disulfonyl chloride.

10. The method for preparing the high-desalination seawater desalination composite reverse osmosis membrane according to claim 1, characterized in that: Includes the following steps: (1) Take a porous support layer and immerse it in a dispersion containing a temperature-sensitive polymer and a highly thermally conductive two-dimensional nanomaterial. After taking it out, dry and solidify it on the porous support layer to form a thermally responsive stress buffer intermediate layer. (2) Coat the surface of the thermally responsive stress buffer intermediate layer formed in step (1) with an aqueous solution containing polyamine and repair microcapsules. After the treatment is completed, remove the residual liquid on the surface. Then coat the same surface with an oil solution containing polyacryl halides. After the treatment is completed, remove the residual liquid on the surface. Heat treatment is performed to form a self-healing polyamide separation layer. Finally, immerse it in an aqueous glycerol solution for treatment. Take it out and dry it to obtain a high desalination seawater desalination composite reverse osmosis membrane.